A Study on the Sense of Place in the CafÃ© dan Restauant â€œTanatap Wall Gardenâ€ Semarang - Fitri, Rizki Dila; Adelline, Salshabilla Shafa; Widiastuti, Kurnia (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2024)
The design of public buildings in general plays an important role in influencing the sensation of a building, in addition to creating an interesting and unique visual impression, affecting the feelings of visitors, and having a positive or negative impact on the environment around the building. One of them is Tanatap Wall Garden which is located on Jl. Madukoro No.4-5, Tawangsari, Semarang City. Tanatap Wall Garden has its own characteristics that distinguish it from the many modern coffee shops in Semarang City. In the background by a well-known architect, Antonius Richard Rusli, as the founder of the RAD+ar (Research Artistic Design + architecture) design group which focuses on the characteristics of the tropical climate in the Indonesian archipelago with innovative designs and contributions to sustainable architecture. The Semarang City Wall Garden is included in one of the design experiments carefully planned by RAD+ar, with the aim of evaluating the performance of commercial spaces in real-world situations that are sustainable. Tanatap Wall Garden Semarang City has a tropical architectural style with natural elements created in it that are adapted from existing site conditions.Â